A study of factors affecting the occurrence of down syndrome in Negeri Sembilan Malaysia - Chigozie, Opara Otuodi (2020)
Due to the fact of the high correlation between advanced maternal age and the risk of Down syndrome, genetic and socio- demographic factors of population are expected to have considerable effect on Down syndrome births. The main objective of this research was to assess the effect of genetic and socio-demographic factors within Malaysia in number and incidences of DS. Three hypothesis were tested using 104 DS data and 204 NDS data in Negeri Sembilan, obtained through questionnaire. The hypothesis tested included whether there is a relationship between DS cases and advanced maternal age in Malaysian population, whether there is relationship between genetic factors and DS cases in Malaysian population and lastly whether there is a relationship between DS cases and certain socio-demographic factors in the Malaysian population. Regression analysis having become a standard statistical tool for analysis, probit model, linear probability model and multiple logistic model were used for analysing DS data against genetic and socio-demographic variables while simple logit and probit models were used to analyze DS data against maternal age. For each analysis, these models were compared using Akaike information criteria to determine the model with the best fit for prediction. The results show a significant relationship between maternal age and DS cases. It was also found that DS is not genetic and cannot be transferred from parent to offspring. Race, place of residence and mothers’ education level were found to have significant influence on occurrence of DS in Malaysia. Paternal age, Smoking habit, pre-natal scan, and heredity were found to be insignificant factors in the occurrence of DS in Malaysia